Cannabidiol Modulates Mitochondrial Redox and Dynamics in MCF7 Cancer Cells: A Study Using Fluorescence Lifetime Imaging Microscopy of NAD(P)H - Mould, Rhys Richard; Botchway, Stanley W.; Parkinson, James R. C.; Thomas, Elizabeth Louise; Guy, Geoffrey W; Bell, Jimmy D.; Nunn, Alistair V. W. (Frontiers in Molecular Biosciences, 2021)
The cannabinoid, cannabidiol (CBD), is part of the plant's natural defence system that when given to animals has many useful medicinal properties, including activity against cancer cells, modulation of the immune system, and efficacy in epilepsy. Although there is no consensus on its precise mode of action as it affects many cellular targets, CBD does appear to influence mitochondrial function. This would suggest that there is a cross-kingdom ability to modulate stress resistance systems that enhance homeostasis. As NAD(P)H autofluorescence can be used as both a metabolic sensor and mitochondrial imaging modality, we assessed the potential of this technique to study the in vitro effects of CBD using 2-photon excitation and fluorescence lifetime imaging microscopy (2P-FLIM) of NAD(P)H against more traditional markers of mitochondrial morphology and cellular stress in MCF7 breast cancer cells. 2P-FLIM analysis revealed that the addition of CBD induced a dose-dependent decrease in bound NAD(P)H, with 20 µM treatments significantly decreasing the contribution of bound NAD(P)H by 14.6% relative to control (p<0.001). CBD also increased mitochondrial concentrations of reactive oxygen species (ROS) (160 ± 53 vs. 97.6 ± 4.8%, 20 µM CBD vs. control, respectively, p<0.001) and Ca2+ (187 ± 78 vs. 105 ± 10%, 20 µM CBD vs. control, respectively, p<0.001); this was associated with significantly decreased mitochondrial branch length and increased fission. These are all suggestive of mitochondrial stress. Our results support the use of NAD(P)H autofluorescence as an investigative tool and provide further evidence that CBD can modulate mitochondrial function and morphology in a dose dependent manner, with clear evidence of it inducing oxidative stress at higher concentrations. This continues to support emerging data in the literature and may provide further insight into its overall mode of action, not only in cancer, but potentially its function in the plant and why it can act as a medicine.